E-211 Rapid prototyping and evaluation of 3d catheter tip shapes in a silicone transradial aortic arch model. (23rd July 2022) - Boyle, J; Zerebiec, K; Silveira, L; Muse, J; Kreuser, G; Paris, T; Floreani, R; Johnson, D; Raymond, S
Abstract : Introduction/Purpose: Pre-shaped neuroangiography catheters have shapes constrained to the 2D plane despite the complex 3D geometry of the arch and great vessels. 3D shapes may enable more efficient and safer selection of the great vessels when accessing the arch from a radial approach. We developed a process for generating arbitrary tip shapes, created two 3D variations of the classic Simmons 2, and tested the performance of these catheters in a silicone aortic arch model. Materials and Methods: The standard reverse curve catheter shape was used as a rubric for channel-based heat shaping forms. Right- and left-handed (LH and RH) forms were designed in Onshape by taking the baseline shape and turning the distal tip 90 degrees into or out of the plane (see figure 1 ). The forms were 3D printed in aluminum by Shapeways. A 2D baseline form was created using the standard reverse curve shape. Straight 5 Fr Terumo GLIDECATH catheters were used as stock, heated in the forms at 160 degrees Celsius for 15 minutes, and rapidly quenched in a room temperature water bath. Catheter performance was evaluated with two tasks: catheter reformation at the arch and great vessel selection from the arch. Three trainee operators performed 10 timed trials of each task with each catheter. Results: The LH catheter reformation times were similar to the Simmons 2 for two operators (all values in median (IQR): operator A, 12s (9–15) vs 24s (13.5–29.75), operator B, 16s (12.25–20) vs 13s (12.25–26.5)), but slower for the third operator (operator C, 16s (13.25–20.25) vs 9.5s (9–10.75). Selection of the left common carotid and right vertebral arteries was similar to slightly faster for all operators and selection of the right common carotid and left vertebral arteries was similar to slightly slower with the LH catheter compared to the Simmons 2. The RH catheter performed significantly slower than the Simmons 2 and LH catheter for all tasks and operators, and no operator was able to select the left vertebral artery with the RH catheter. Conclusion: 3D catheter shapes can be rapidly prototyped with 3D printed aluminum forms and evaluated in a silicone aortic arch model. In our preliminary trial, the left-handed catheter was comparable to the standard Simmons 2 for most maneuvers and even faster for selection of certain vessels. The right-handed catheter was inferior for all maneuvers. Disclosures: J. Boyle: None. K. Zerebiec: None. L. Silveira: None. J. Muse: None. G. Kreuser: None. T. Paris: None. R. Floreani: None. D. Johnson: None. S. Raymond: None.